Effect of habitat conditions and plant traits on leaf damage in the Carduoideae subfamily - Münzbergová, Zuzana; Skuhrovec, Jiří (PloS one, 2013)
Plant traits are the key factors that determine herbivore foraging selection. The traits serving as defense traits against herbivores represent a wide range of traits, such as chemical, physiological, morphological and life-history traits. While many studies considered plant defense traits at the within-species scale, much less is known from comparisons of a wide range of closely related species. The aim of this study was to identify factors responsible for the intensity of leaf damage in the Carduoideae subfamily of Asteraceae, which hosts many invasive species and thus is potential candidate plant species that could be controlled by biological control. Specifically, we wanted to see the relative importance of habitat characteristics, plant size and plants traits in determining the degree of folivory. The study identified several defense traits able to explain differences in herbivory between species after accounting for differences in the habitats in which the species occur and the plant size. Specifically, the most important traits were traits related to the quality of the leaf tissue expressed as the content of phosphorus, water and specific leaf area, which suggests that the leaf quality had a more important effect on the degree of herbivory than the presence of specific defense mechanisms such as spines and hair. Leaf quality is thus a candidate factor that drives herbivore choice when selecting which plant to feed on and should be considered when assessing the danger that a herbivore will switch hosts when introduced to a new range.
Keywords: listy rostlin; ekosystém; Asteraceae; Ecosystem; Plant Leaves